Challenges and opportunities of natural biomaterials for advanced devices and therapies - Reis, R. L. (2016)
Natural biomaterials attracted an early interest from the clinical community as the basis for the production of medical devices and prostheses. It is widely recognized that nature has developed many elegant materials covering a wide range of mechanical, biological and chemical requirements. Natural materials have properties ranging from very stiff and strong such as dentin or bone, to very soft and compliant materials such as skin or fat. Natural biomaterials are usually biodegradable and can be remodeled by existing proteases and enzymes. This characteristic can be explored for the development of advanced medical devices and therapies that require only temporary remodeling of the implant site or resorbability. One of the most evident opportunities in studying natural biomaterials for biomedical applications is the wealth of unexplored natural biomaterials that can have an important role in advanced biomedical applications and therapies.